Air transport and tourism flows to islands: A panel analysis for southern European countries. (5th April 2022) - Mazzola, Fabio; Cirà, Andrea; Ruggieri, Giovanni; Butler, Richard
Abstract: Air transport is an essential component of the tourism industry, and the number, frequency, and capacity of flight connections may influence the level of tourism demand, especially for island destinations. This paper evaluates the influence of air transport on tourism arrivals to selected islands in seven southern European Union countries to determine the nature of the relationship between tourist arrivals and air transport, specifically, whether air transport services generate tourism demand or merely enable touristic flows. The paper uses panel data and applies an econometric model with justifications for endogeneity and dynamic issues. Results show a moderate impact of transport infrastructures on generating additional tourist arrivals; however, the model shows that air transport is a prerequisite to developing tourism demand and is not the only determinant in increasing tourist arrivals. Tourist arrivals appear more a determinant than a consequence of changes in‐flight connections.